2011
DOI: 10.1002/er.1901
|View full text |Cite
|
Sign up to set email alerts
|

Effects of ambient conditions on the thermodynamic performance of hybrid nuclear-combined cycle power plant

Abstract: SUMMARY This paper provides a theoretical study of the effects of ambient conditions on the thermodynamic performance of a hybrid combined‐nuclear cycle power plant. The operational parameters investigated are based on the first and second laws of thermodynamics, which include the ambient air temperature and ambient relative humidity (Φ). The results obtained for the gas turbine model are shown to agree very well with operational data from the Al‐Zour Emergency power plant in Kuwait. The ambient temperature wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…[44][45][46][47][48][49][50] Previous studies of the fire experiment in low-altitude or low-pressure chamber have a certain significance for aircraft aviation safety because the pressure change during air transport is the same order of magnitudes with those experiments. [51][52][53][54][55][56] However, the research on the fire characteristics of the energy-containing LIB in low ambient pressure is currently insufficient. On the basis of the above considerations, LIBs were experimentally tested at two ambient pressures, ie, 100.8 kPa (Hefei China, altitude 20 m) and 64.3 kPa (Lhasa China, altitude 3650 m).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[44][45][46][47][48][49][50] Previous studies of the fire experiment in low-altitude or low-pressure chamber have a certain significance for aircraft aviation safety because the pressure change during air transport is the same order of magnitudes with those experiments. [51][52][53][54][55][56] However, the research on the fire characteristics of the energy-containing LIB in low ambient pressure is currently insufficient. On the basis of the above considerations, LIBs were experimentally tested at two ambient pressures, ie, 100.8 kPa (Hefei China, altitude 20 m) and 64.3 kPa (Lhasa China, altitude 3650 m).…”
Section: Discussionmentioning
confidence: 99%
“…Experimental and theoretical analysis results indicated that the pressure affects fire behaviors by changing the ignition, temperature, mass loss fraction, heat flux, heat release rate (HRR), combustion efficiency, and so on . Previous studies of the fire experiment in low‐altitude or low‐pressure chamber have a certain significance for aircraft aviation safety because the pressure change during air transport is the same order of magnitudes with those experiments . However, the research on the fire characteristics of the energy‐containing LIB in low ambient pressure is currently insufficient.…”
Section: Introductionmentioning
confidence: 99%
“…Rashid et al presented a particle swarm optimization trained feed-forward neural network approach to predict power plant output [23]. Alsairafi examined the effect of ambient conditions on the thermodynamic performance of a hybrid combined-nuclear cycle power plant [24]. Al-Fahed investigated the effect of increased inlet air temperature and relative humidity on the performance of a gas turbine cogeneration system [25].…”
Section: Pp S809-s817mentioning
confidence: 99%
“…Recent work and study on nuclear desalination show that the integration of conventional desalination plants with nuclear installations is practicable and is now a developed technology that can be beneficial for meeting the fresh water demands worldwide. The new perspective of the nuclear desalination processes will ensure reduction in the use of fossil fuel .…”
Section: Introductionmentioning
confidence: 99%